On Symbolic 2-Plithogenic Hyperbolic Functions - Ahmad A. Abubaker; Nedal Tahat; Sara A. Khalil; Khaled Matarneh; Mutaz Shatnawi; Ahmed Atallah Alsaraireh; P. Prabakaran; Abdallah Al-Husban (Neutrosophic Sets and Systems)
In this article, we have introduced and studied the concept of symbolic 2-plithogenic hyperbolic functions and the symbolic 2-plithogenic identities. Also, we have discussed the derivatives and integrals of the symbolic 2-plithogenic hyperbolic functions and presented the logarithmic forms of the inverse symbolic 2-plithogenic hyperbolic functions.